Cybersecurity Dilemmas: Technology, Policy, and Incentives: Summary of Discussions at the 2014 Raymond and Beverly Sackler U.S.-U.K. Scientific Forum - National Academy of Sciences
Individuals, businesses, governments, and society at large have tied their future to information technologies, and activities carried out in cyberspace have become integral to daily life. Yet these activities - many of them drivers of economic development - are under constant attack from vandals, criminals, terrorists, hostile states, and other malevolent actors. In addition, a variety of legitimate actors, including businesses and governments, have an interest in collecting, analyzing, and storing information from and about individuals and organizations, potentially creating security and privacy risks. Cybersecurity is made extremely difficult by the incredible complexity and scale of cyberspace. The challenges to achieving cybersecurity constantly change as technologies advance, new applications of information technologies emerge, and societal norms evolve. In our interconnected world, cyberspace is a key topic that transcends borders and should influence (as well as be influenced by) international relations. As such, both national and international laws will need careful evaluation to help ensure the conviction of cybercriminals, support companies that work internationally, and protect national security. On December 8 and 9, 2014, the Raymond and Beverly Sackler U.S.-U.K. Scientific Forum \

Making the Nation Safer: The Role of Science and Technology in Countering Terrorism - National Research Council
Vulnerabilities abound in U.S. society. The openness and efficiency of our key infrastructures 2014 transportation, information and telecommunications systems, health systems, the electric power grid, emergency response units, food and water supplies, and others 2014 make them susceptible to terrorist attacks. Making the Nation Safer discusses technical approaches to mitigating these vulnerabilities. A broad range of topics are covered in this book, including: Nuclear and radiological threats, such as improvised nuclear devices and \

Decrypting the Encryption Debate: A Framework for Decision Makers - National Academies of Sciences, Engineering,; Medicine
Encryption protects information stored on smartphones, laptops, and other devices - in some cases by default. Encrypted communications are provided by widely used computing devices and services - such as smartphones, laptops, and messaging applications - that are used by hundreds of millions of users. Individuals, organizations, and governments rely on encryption to counter threats from a wide range of actors, including unsophisticated and sophisticated criminals, foreign intelligence agencies, and repressive governments. Encryption on its own does not solve the challenge of providing effective security for data and systems, but it is an important tool. At the same time, encryption is relied on by criminals to avoid investigation and prosecution, including criminals who may unknowingly benefit from default settings as well as those who deliberately use encryption. Thus, encryption complicates law enforcement and intelligence investigations. When communications are encrypted \

Foundational Cybersecurity Research: Improving Science, Engineering, and Institutions - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Attaining meaningful cybersecurity presents a broad societal challenge. Its complexity and the range of systems and sectors in which it is needed mean that successful approaches are necessarily multifaceted. Moreover, cybersecurity is a dynamic process involving human attackers who continue to adapt. Despite considerable investments of resources and intellect, cybersecurity continues to poses serious challenges to national security, business performance, and public well-being. Modern developments in computation, storage and connectivity to the Internet have brought into even sharper focus the need for a better understanding of the overall security of the systems we depend on. Foundational Cybersecurity Research focuses on foundational research strategies for organizing people, technologies, and governance. These strategies seek to ensure the sustained support needed to create an agile, effective research community, with collaborative links across disciplines and between research and practice. This report is aimed primarily at the cybersecurity research community, but takes a broad view that efforts to improve foundational cybersecurity research will need to include many disciplines working together to achieve common goals.

Beyond Spectre: Confronting New Technical and Policy Challenges: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
In 2017, researchers discovered a vulnerability in microprocessors used in computers and devices all over the world. The vulnerability, named Spectre, combines side effects from caching and speculative execution, which are techniques that have been used for many years to increase the speed at which computers operate. The discovery upends a number of common assumptions about cybersecurity and draws attention to the complexities of the global supply chain and global customer base for the vast range of devices and cloud capabilities that all computer users rely on. In October 2018, the Forum on Cyber Resilience hosted a workshop to explore the implications of this development. This publication summarizes the presentations and discussions from the workshop.

Looking Ahead at the Cybersecurity Workforce at the Federal Aviation Administration - National Academies of Sciences, Engineering,; Medicine
The Federal Aviation Administration (FAA) has overseen significant upgrades to the technology used to manage aviation operations to increase the safety and efficiency of the National Airspace System (NAS). Though necessary to regular operations, these modern computing and communications systems provide a greater attack surface for criminals, terrorists, or nation-states to exploit and thereby increase the potential for cybersecurity threats to the NAS and its constituents. The future safety and security of air travel will rely in part on the ability of the FAA to build a workforce capable of addressing the evolving cybersecurity threat landscape. Securing the computers, networks, and data that underpin modern aviation depends in part on the FAA having enough cybersecurity professionals (capacity) with the right knowledge, skills, and abilities (capability)). It also depends on the FAA's workforce having sufficient diversity of backgrounds and experience. Such diversity is critical in analyzing cybersecurity problems and widely understood to be a \

Technology, Policy, Law, and Ethics Regarding U.S. Acquisition and Use of Cyberattack Capabilities - National Research Council (The National Academies Press, 2009)
The United States is increasingly dependent on information and information technology for both civilian and military purposes, as are many other nations. Although there is a substantial literature on the potential impact of a cyberattack on the societal infrastructure of the United States, little has been written about the use of cyberattack as an instrument of U.S. policy. Cyberattacks–actions intended to damage adversary computer systems or networks–can be used for a variety of military purposes. But they also have application to certain missions of the intelligence community, such as covert action. They may be useful for certain domestic law enforcement purposes, and some analysts believe that they might be useful for certain private sector entities who are themselves under cyberattack. This report considers all of these applications from an integrated perspective that ties together technology, policy, legal, and ethical issues. Focusing on the use of cyberattack as an instrument of U.S. national policy, Technology, Policy, Law and Ethics Regarding U.S. Acquisition and Use of Cyberattack Capabilities explores important characteristics of cyberattack. It describes the current international and domestic legal structure as it might apply to cyberattack, and considers analogies to other domains of conflict to develop relevant insights. Of special interest to the military, intelligence, law enforcement, and homeland security communities, this report is also an essential point of departure for nongovernmental researchers interested in this rarely discussed topic.

Update of Security 101: A Physical Security and Cybersecurity Primer for Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Since 2009, when NCHRP's last Security 101 report was released, there have been significant advances in transportation security approaches, including new strategies, programs, and ways of doing business that have increased the security of transportation systems as well as ensured their resiliency.Hazards and threats to the system have also continued to evolve since 2009. While the incidence of large-scale terrorist attacks has remained small, transportation agencies are at increasingly greater risk from system-disrupting events due to natural causes, unintentional human intervention, and intentional criminal acts, such as active-shooter incidents. Cyber risks also are increasing and can impact not only data, but the control systems2014like tunnel-ventilation systems2014operated by transportation agencies.>The TRB National Cooperative Highway Research Program's NCHRP Research Report 930: Update of Security 101: A Physical Security and Cybersecurity Primer for Transportation Agencies provides valuable information about current and accepted practices associated with both physical and cyber security and its applicability to surface transportation.The report is accompanied by a PowerPoint for the project and NCHRP Web-Only Document 266: Developing a Physical and Cyber Security Primer for Transportation Agencies.

Who Goes There?: Authentication Through the Lens of Privacy - National Research Council (The National Academies Press, 2003)
Who Goes There?: Authentication Through the Lens of Privacy explores authentication technologies (passwords, PKI, biometrics, etc.) and their implications for the privacy of the individuals being authenticated. As authentication becomes ever more ubiquitous, understanding its interplay with privacy is vital. The report examines numerous concepts, including authentication, authorization, identification, privacy, and security. It provides a framework to guide thinking about these issues when deciding whether and how to use authentication in a particular context. The book explains how privacy is affected by system design decisions. It also describes government2019s unique role in authentication and what this means for how government can use authentication with minimal invasions of privacy. In addition, Who Goes There? outlines usability and security considerations and provides a primer on privacy law and policy.

Information Technology for Counterterrorism: Immediate Actions and Future Possibilities - National Research Council (The National Academies Press, 2003)
Information technology (IT) is essential to virtually all of the nation2019s critical infrastructures making them vulnerable by a terrorist attack on their IT system. An attack could be on the system itself or use the IT system to launch or exacerbate another type of attack. IT can also be used as a counterterrorism tool. The report concludes that the most devastating consequences of a terrorist attack would occur if it were on or used IT as part of a broader attack. The report presents two recommendations on what can be done in the short term to protect the nation2019s communications and information systems and several recommendations about what can be done over the longer term. The report also notes the importance of considering how an IT system will be deployed to maximize protection against and usefulness in responding to attacks.

At the Nexus of Cybersecurity and Public Policy: Some Basic Concepts and Issues - National Research Council (The National Academies Press, 2014)
We depend on information and information technology (IT) to make many of our day-to-day tasks easier and more convenient. Computers play key roles in transportation, health care, banking, and energy. Businesses use IT for payroll and accounting, inventory and sales, and research and development. Modern military forces use weapons that are increasingly coordinated through computer-based networks. Cybersecurity is vital to protecting all of these functions. Cyberspace is vulnerable to a broad spectrum of hackers, criminals, terrorists, and state actors. Working in cyberspace, these malevolent actors can steal money, intellectual property, or classified information; impersonate law-abiding parties for their own purposes; damage important data; or deny the availability of normally accessible services. Cybersecurity issues arise because of three factors taken together - the presence of malevolent actors in cyberspace, societal reliance on IT for many important functions, and the presence of vulnerabilities in IT systems. What steps can policy makers take to protect our government, businesses, and the public from those would take advantage of system vulnerabilities? At the Nexus of Cybersecurity and Public Policy offers a wealth of information on practical measures, technical and nontechnical challenges, and potential policy responses. According to this report, cybersecurity is a never-ending battle; threats will evolve as adversaries adopt new tools and techniques to compromise security. Cybersecurity is therefore an ongoing process that needs to evolve as new threats are identified. At the Nexus of Cybersecurity and Public Policy is a call for action to make cybersecurity a public safety priority. For a number of years, the cybersecurity issue has received increasing public attention; however, most policy focus has been on the short-term costs of improving systems. In its explanation of the fundamentals of cybersecurity and the discussion of potential policy responses, this book will be a resource for policy makers, cybersecurity and IT professionals, and anyone who wants to understand threats to cyberspace.

Cybersecurity of Freight Information Systems: A Scoping Study – Special Report 274 - Transportation Research Board; National Research Council (The National Academies Press, 2003)
TRB Special Report 274 - Cybersecurity of Freight Information Systems: A Scoping Study reviews trends in the use of information technology in the freight transportation industry and assesses potential vulnerabilities to a cyberattack. Special Report 274 Summary

Professionalizing the Nation's Cybersecurity Workforce?: Criteria for Decision-Making - National Research Council (The National Academies Press, 2013)
Professionalizing the Nation's Cybersecurity Workforce? Criteria for Decision-Making considers approaches to increasing the professionalization of the nation's cybersecurity workforce. This report examines workforce requirements for cybersecurity and the segments and job functions in which professionalization is most needed; the role of assessment tools, certification, licensing, and other means for assessing and enhancing professionalization; and emerging approaches, such as performance-based measures. It also examines requirements for the federal (military and civilian) workforce, the private sector, and state and local government. The report focuses on three essential elements: (1) understanding the context for cybersecurity workforce development, (2) considering the relative advantages, disadvantages, and approaches to professionalizing the nation's cybersecurity workforce, and (3) setting forth criteria that can be used to identify which, if any, specialty areas may require professionalization and set forth criteria for evaluating different approaches and tools for professionalization. Professionalizing the Nation's Cybersecurity Workforce? Criteria for Decision-Making characterizes the current landscape for cybersecurity workforce development and sets forth criteria that the federal agencies participating in the National Initiative for Cybersecurity Education2014as well as organizations that employ cybersecurity workers2014could use to identify which specialty areas may require professionalization and to evaluate different approaches and tools for professionalization.

Software for Dependable Systems: Sufficient Evidence? - National Research Council (The National Academies Press, 2007)
The focus of Software for Dependable Systems is a set of fundamental principles that underlie software system dependability and that suggest a different approach to the development and assessment of dependable software. Unfortunately, it is difficult to assess the dependability of software. The field of software engineering suffers from a pervasive lack of evidence about the incidence and severity of software failures; about the dependability of existing software systems; about the efficacy of existing and proposed development methods; about the benefits of certification schemes; and so on. There are many anecdotal reports, which2014although often useful for indicating areas of concern or highlighting promising avenues of research2014do little to establish a sound and complete basis for making policy decisions regarding dependability. The committee regards claims of extraordinary dependability that are sometimes made on this basis for the most critical of systems as unsubstantiated, and perhaps irresponsible. This difficulty regarding the lack of evidence for system dependability leads to two conclusions: (1) that better evidence is needed, so that approaches aimed at improving the dependability of software can be objectively assessed, and (2) that, for now, the pursuit of dependability in software systems should focus on the construction and evaluation of evidence. The committee also recognized the importance of adopting the practices that are already known and used by the best developers; this report gives a sample of such practices. Some of these (such as systematic configuration management and automated regression testing) are relatively easy to adopt; others (such as constructing hazard analyses and threat models, exploiting formal notations when appropriate, and applying static analysis to code) will require new training for many developers. However valuable, though, these practices are in themselves no silver bullet, and new techniques and methods will be required in order to build future software systems to the level of dependability that will be required.

Software Update as a Mechanism for Resilience and Security: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Software update is an important mechanism by which security changes and improvements are made in software, and this seemingly simple concept encompasses a wide variety of practices, mechanisms, policies, and technologies. To explore the landscape further, the Forum on Cyber Resilience hosted a workshop featuring invited speakers from government, the private sector, and academia. This publication summarizes the presentations and discussions from the workshop.

Biometric Recognition: Challenges and Opportunities - National Research Council (The National Academies Press, 2010)
Biometric recognition–the automated recognition of individuals based on their behavioral and biological characteristic–is promoted as a way to help identify terrorists, provide better control of access to physical facilities and financial accounts, and increase the efficiency of access to services and their utilization. Biometric recognition has been applied to identification of criminals, patient tracking in medical informatics, and the personalization of social services, among other things. In spite of substantial effort, however, there remain unresolved questions about the effectiveness and management of systems for biometric recognition, as well as the appropriateness and societal impact of their use. Moreover, the general public has been exposed to biometrics largely as high-technology gadgets in spy thrillers or as fear-instilling instruments of state or corporate surveillance in speculative fiction. Now, as biometric technologies appear poised for broader use, increased concerns about national security and the tracking of individuals as they cross borders have caused passports, visas, and border-crossing records to be linked to biometric data. A focus on fighting insurgencies and terrorism has led to the military deployment of biometric tools to enable recognition of individuals as friend or foe. Commercially, finger-imaging sensors, whose cost and physical size have been reduced, now appear on many laptop personal computers, handheld devices, mobile phones, and other consumer devices. Biometric Recognition: Challenges and Opportunities addresses the issues surrounding broader implementation of this technology, making two main points: first, biometric recognition systems are incredibly complex, and need to be addressed as such. Second, biometric recognition is an inherently probabilistic endeavor. Consequently, even when the technology and the system in which it is embedded are behaving as designed, there is inevitable uncertainty and risk of error. This book elaborates on these themes in detail to provide policy makers, developers, and researchers a comprehensive assessment of biometric recognition that examines current capabilities, future possibilities, and the role of government in technology and system development.

Proceedings of a Workshop on Deterring Cyberattacks: Informing Strategies and Developing Options for U.S. Policy - National Research Council (The National Academies Press, 2010)
In a world of increasing dependence on information technology, the prevention of cyberattacks on a nation's important computer and communications systems and networks is a problem that looms large. Given the demonstrated limitations of passive cybersecurity defense measures, it is natural to consider the possibility that deterrence might play a useful role in preventing cyberattacks against the United States and its vital interests. At the request of the Office of the Director of National Intelligence, the National Research Council undertook a two-phase project aimed to foster a broad, multidisciplinary examination of strategies for deterring cyberattacks on the United States and of the possible utility of these strategies for the U.S. government. The first phase produced a letter report providing basic information needed to understand the nature of the problem and to articulate important questions that can drive research regarding ways of more effectively preventing, discouraging, and inhibiting hostile activity against important U.S. information systems and networks. The second phase of the project entailed selecting appropriate experts to write papers on questions raised in the letter report. A number of experts, identified by the committee, were commissioned to write these papers under contract with the National Academy of Sciences. Commissioned papers were discussed at a public workshop held June 10-11, 2010, in Washington, D.C., and authors revised their papers after the workshop. Although the authors were selected and the papers reviewed and discussed by the committee, the individually authored papers do not reflect consensus views of the committee, and the reader should view these papers as offering points of departure that can stimulate further work on the topics discussed. The papers presented in this volume are published essentially as received from the authors, with some proofreading corrections made as limited time allowed.

Toward a Safer and More Secure Cyberspace - National Research Council; National Academy of Engineering (The National Academies Press, 2007)
Given the growing importance of cyberspace to nearly all aspects of national life, a secure cyberspace is vitally important to the nation, but cyberspace is far from secure today. The United States faces the real risk that adversaries will exploit vulnerabilities in the nation2019s critical information systems, thereby causing considerable suffering and damage. Online e-commerce business, government agency files, and identity records are all potential security targets. Toward a Safer and More Secure Cyberspace examines these Internet security vulnerabilities and offers a strategy for future research aimed at countering cyber attacks. It also explores the nature of online threats and some of the reasons why past research for improving cybersecurity has had less impact than anticipated, and considers the human resource base needed to advance the cybersecurity research agenda. This book will be an invaluable resource for Internet security professionals, information technologists, policy makers, data stewards, e-commerce providers, consumer protection advocates, and others interested in digital security and safety.

Critical Code: Software Producibility for Defense - National Research Council (The National Academies Press, 2010)
Critical Code contemplates Department of Defense (DoD) needs and priorities for software research and suggests a research agenda and related actions. Building on two prior books2014Summary of a Workshop on Software Intensive Systems and Uncertainty at Scale and Preliminary Observations on DoD Software Research Needs and Priorities2014the present volume assesses the nature of the national investment in software research and, in particular, considers ways to revitalize the knowledge base needed to design, produce, and employ software-intensive systems for tomorrow's defense needs. Critical Code discusses four sets of questions: To what extent is software capability significant for the DoD? Is it becoming more or less significant and strategic in systems development? Will the advances in software producibility needed by the DoD emerge unaided from industry at a pace sufficient to meet evolving defense requirements? What are the opportunities for the DoD to make more effective use of emerging technology to improve software capability and software producibility? In which technology areas should the DoD invest in research to advance defense software capability and producibility?

Securing the Vote: Protecting American Democracy - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2018)
During the 2016 presidential election, America's election infrastructure was targeted by actors sponsored by the Russian government. Securing the Vote: Protecting American Democracy examines the challenges arising out of the 2016 federal election, assesses current technology and standards for voting, and recommends steps that the federal government, state and local governments, election administrators, and vendors of voting technology should take to improve the security of election infrastructure. In doing so, the report provides a vision of voting that is more secure, accessible, reliable, and verifiable.